Accounting for van der Waals interactions between adsorbates and surfaces in density functional theory based calculations: selected examples - Prates Ramalho, Joao P. (2017)
This article reviews the different density functional theory (DFT) methods available in the literature for dealing with dispersion interactions and recent applications of DFT approaches including van der Waals corrections in the study of the interaction of atoms and molecules with several different surfaces. Focus is given to the interaction of atoms and molecules with metal, metal oxide and graphite surfaces or more complex systems. It will be shown that DFT approaches including van der Waals corrections present significant advances over standard exchange-correlation functionals for treating systems dominated by weak interactions.